Synergistic effects of 1-MCP and H₂S co-treatment on sugar and energy metabolisms in postharvest strawberry fruit - Wang, Xingyue; Qiu, Tian; Jiang, JingJing; Shi, Kaili; Liu, Zhikang; Wang, YanYan; Song, Qingyuan; Zhang, Chen; Wu, Tingyu; Chen, Dan; Yang, Xiaohui; Liu, Fang; et al. (Frontiers in Nutrition, 2025)
Introduction1-methylcyclopropene (1-MCP) and hydrogen sulfide (H2S) play important roles in the ripening and senescence of postharvest fruits and vegetables. However, little knowledge was available for the effect of the combined treatment of 1-MCP and H2S on the quality maintenance of postharvest strawberry fruit.MethodsThe synergistic effects of 1.0 μL L−1 1-MCP and 0.8 mmol L−1 sodium hydrosulfide (NaHS, H2S donor) combined treatment on the sugar and energy metabolisms of strawberry fruit during cold storage at 4 ± 0.5°C with a relative humidity of 80–85% for 15 d were studied.ResultsThe results showed that the combined treatment effectively suppressed the increase of decay rate, decay index, and weight loss rate while maintaining the firmness and visual quality of strawberry fruit compared to the 1-MCP or H2S treatment. Moreover, the combined treatment maintained higher sucrose content and lower contents of glucose and fructose by inhibiting the activities of acid invertase (AI) and neutral invertase (NI), while enhancing the activities of sucrose synthase (SS) and sucrose phosphate synthase (SPS). Meanwhile, strawberry fruit treated with the combination elevated ATP levels and energy charge by upregulating key enzymes in energy metabolism, including succinate dehydrogenase (SDH), cytochrome c oxidase (CCO), H+-adenosine triphosphatase (ATPase) and Ca2+-ATPase.ConclusionThese results indicated that 1-MCP and H₂S acted synergistically to regulate sugar catabolism and energy homeostasis, promoting elevated sucrose accumulation and mitochondrial energy production, thereby maintaining the integrity of cell structure and the quality of strawberry fruit.